Salmonella typhimurium virulence in a burned-mouse model. - Carsiotis, M (1989)
Various features of salmonellosis were examined in a burned-mouse model. In this model, which uses an outbred mouse strain, a challenge dose of ca. 100 CFU with any of several strains of Salmonella typhimurium caused a fatal infection. A variety of mutated strains attenuated for virulence in Salmonella-susceptible parenterally infected mice were also attenuated in the burned-mouse model. When administered as live vaccines injected intraperitoneally the same attenuated strains provided between slight and complete protection against subsequent lethal challenge subcutaneously at the site of a burn. The correspondence of results obtained in the burned-mouse model with those seen in other mouse models coupled with the unique advantages of the burned-mouse model argue for the usefulness of the model in studies of salmonellosis and in testing of strains constructed for use as live vaccines.